Constructing ultraporous covalent organic fameworks in seconds via an organic terracotta process - Karak, S.; Kandambeth, S.; Biswal, B. P.; Sasmal, H. S.; Kumar, S.; Pachfule, P.; Banerjee, R. (Journal of the American Chemical Society, 2017)
Research on covalent organic frameworks (COFs) has recently gathered significant momentum by the virtue of their predictive design, controllable porosity, and long-range ordering. However, the lack of solvent-free and easy-to-perform synthesis processes appears to be the bottleneck toward their greener fabrication, thereby limiting their possible potential applications. To alleviate such shortcomings, we demonstrate a simple route toward the rapid synthesis of highly crystalline and ultraporous COFs in seconds using a novel salt-mediated crystallization approach. A high degree of synthetic control in interlayer stacking and layer planarity renders an ordered network with a surface area as high as 3000 m(2) g-(1). Further, this approach has been extrapolated for the continuous synthesis of COFs by means of a twin screw extruder and in situ processes of COFs into different shapes mimicking the ancient terracotta process. Finally, the regular COF beads are shown to outperform the leading zeolites in water sorption performance, with notably facile regeneration ability and structural integrity.